Cytokines and Chemokines in Irritant Contact Dermatitis - Haur Yueh Lee; Marco Stieger; Nikhil Yawalkar; Masato Kakeda (Hindawi Limited, 2013)
Irritant contact dermatitis is a result of activated innate immune response to various external stimuli and consists of complex interplay which involves skin barrier disruption, cellular changes, and release of proinflammatory mediators. In this review, we will focus on key cytokines and chemokines involved in the pathogenesis of irritant contact dermatitis and also contrast the differences between allergic contact dermatitis and irritant contact dermatitis.